KARAKTERISTIK HABITAT RHIZANTHES ZIPPELII DI GUNUNG POTENG CAGAR ALAM RAYA PASI KOTA SINGKAWANG KALIMANTAN BARAT - kurniasih, dewi; Astiani, Dwi; Dewantara, Iswan (JURNAL HUTAN LESTARI, 2021)
Rhizanthes zippelii isÂ one of the flora species found in the Pasi Gunung Poteng Nature Reserve area of West Kalimantan.Â Habitat characteristics for this species need to be studied considering that this plant very much depend on the host Tetrastigma to obtain food nutrients during its life cycle.Â The purpose of the research was to describe the habitat characteristicsÂ of Rhizanthes zippeliiÂ in the Area of Gunung Poteng Pasi Nature Reserve and provide information on the types of plants that hostÂ Rhizanthes zippeliiÂ in Gunung Poteng Pasi Nature Reserve.Â The research wasÂ conducted byÂ survey methodÂ in theÂ fieldÂ by sampling using a doubleÂ plot that isÂ placed purposively. Data collected in the form of biotic and abiotic components of the habitat.Â From the five plots of Â observations there was foundÂ 189 individuals of R.zippelii which were in the form of buds, individuals blooming and rotting stages.Â The host plant of this species isÂ Tetrastigma pisicarpum.Â In the natureÂ with hosts plants, it froms a small group of population consisting of several individuals and in this nature reserve was found at an altitude of 423-484 meters above slopes ranging 15.8-36.4%.Â The ambient temperature ranges from 24-25C with a relative humidity of 80-99%.Keywords: Habitat characteristics, Host Tetrastigma, Rhizanthes zippeliiÂ AbstrakRhizanthes zippelii termasuk salah satu spesies flora yang terdapat pada kawasan Cagar Alam Raya Pasi Gunung Poteng Kalimantan Barat. Karakteristik habitat untuk spesies ini perlu dilakukan mengingat tumbuhan ini sangat tergantung kepada inang Tetrastigma untuk mendapatkan nutrisi makanan selama hidupnya. Tujuan dari penelitian yang dilakukan adalah untuk mendeskripsikan karakteristik habitat Rhizanthes zippelii di kawasan Gunung Poteng Cagar Alam Raya Pasi serta memberikan informasi mengenai jenis tumbuhan yang menjadi inang dari Rhizanthes zippelii di Gunung Poteng Cagar Alam Raya Pasi. Penelitian dilakukan dengan metode survey di lapangan dengan pengambilan contoh Â menggunakan petak ganda yang diletakkan secara purposive, data yang diukur berupa komponen biotik dan abiotik pada habitat. Pengukuran pada 5 plot pengamatan pada jenis R.zippelii, ditemukan 189 individu baik itu yang masih berupa kuncup, individu mekar dan membusuk. Tumbuhan inang dari spesies ini yaitu Tetrastigma pisicarpum. R.zippelii dengan inang membentuk populasi kecil yang terdiri dari beberapa individu dan di cagar alam ini ditemukan pada ketinggian 423-484 Mdpl dengan kelerengan 15,8-36,4%. Suhu udara berkisar antara 24-25â°C dengan kelembapan relatif 80-99%.Kata kunci : Karakteristik Habitat, Inang Tetrastigma, Rhizanthes zippelii